EL ENFOQUE CENTRADO EN LA PERSONA COMO HERRAMIENTA DE MEJORA EN LA GESTIÓN DEL TALENTO HUMANO - Ciófalo-Lagos, María Eugenia; González-Pérez, Manuel (European Scientific Journal, ESJ, 2014)
In today’s organizations, is relatively new, to call "talent management" to "the personnel management" and a focus in human capital has been the practice of the last two decades. This approach has unleashed competitive advantage in business. This research deals with the design and validation of a tool based on the definitions of Rogers in order to measure the organizational climate of the area Graduate of an Educational Institution. In general, it is analyzing each worker feel about their immediate boss. We measure the variables: Empathy, Unconditional Acceptance, Consideration and Positive Congruence (E-UA-C-PC), for which a questionnaire was designed to measure the Person Centered Approach (PCA) that won a Cronbach Alpha of 0.913. The results showed reliably and validity that, this questionnaire can measure the work environment.